Strategic responses for a sustainable future : new research in international management - Andersen, Torben Juul (Emerald studies in global strategic responsiveness., 2021)
The past decade has seen global business conditions affected by major socio-economic crises. These have highlighted a pressing need to build resilient organizational structures with effective responsive processes. Businesses are more exposed to uncertain and unknown factors, as well as significant environmental exposures, making the call for resilient and responsive capabilities ever more urgent. The ability to engage in responsive strategy-making under rapid and potentially extreme environmental changes requires a leadership approach that prioritises specialized experiential knowledge of internal and external stakeholders and a capacity to develop organizational settings that enable collaborative ways of working. Strategic Responses for a Sustainable Future considers how modern organizations can respond to deal with increasingly uncertain environmental conditions. Chapters cover adaptive processes to enhance responsiveness, the adoption of green and open strategies, as well as "maverick" methods of resource management and driving innovation, all with the aim of creating effective solutions that can sustain business growth and performance.